2005
DOI: 10.1063/1.2035321
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized injection-locked laser using microelectromechanical systems technology

Abstract: This letter reports a miniaturized injection-locked laser (ILL) using the microelectromechanical systems (MEMS) technology. The device is formed by the integration of a MEMS grated-tuned laser and a Fabry–Perot multimode laser within dimensions of 3mm×2mm×0.6mm. A movable prism serves for both active alignment and optical isolation. Single injection and multiple injections to the slave laser are both tested, it has achieved a side mode suppression ratio of 55dB, a range of fully locked state of 0.16nm and a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Another photonic device was also first presented by the integration of several MEMS components into a functional subsystem [10]. It is a miniaturized injection-locked laser (ILL) that consists of a MEMS grated-tuned laser and a Fabry-Pérot multimode laser within dimensions of 3 mm × 2 mm × 0.6 mm as shown in Fig.…”
Section: Mems Injection-locked Laser Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another photonic device was also first presented by the integration of several MEMS components into a functional subsystem [10]. It is a miniaturized injection-locked laser (ILL) that consists of a MEMS grated-tuned laser and a Fabry-Pérot multimode laser within dimensions of 3 mm × 2 mm × 0.6 mm as shown in Fig.…”
Section: Mems Injection-locked Laser Systemsmentioning
confidence: 99%
“…The 14th International Conference on Solid-State Sensors, Actuators and Microsystems, Lyon, France, June [10][11][12][13][14]2007 presence/absence can be used to determine the cell's RI and size. Experiment on kidney cancer cells measures an effective RI of 1.399 at 0.1% accuracy.…”
Section: Transducers and Eurosensors '07mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conventional injection-locked lasers (ILLs) are bulky and require complicated driving and adjusting mechanism. A simple way of forming the injection-locked laser might be through the microelectromechanical systems (MEMS) technology [7][8]. Previous studies have shown the physical properties of the injection locking, including optical spectrum change, locking depth and drifting of peak wavelength in the steady state.…”
Section: Introductionmentioning
confidence: 99%